Toxicidade da deltametrina (formulação Butox® CE25) nas respostas cardio-respiratórias da tilápia-do-Nilo (Oreochromis niloticus) - Silva, Aline Callegari (2011)
Deltamethrin is a synthetic pyrethroid pesticide, type II, considered of low persistence in the environment and widely utilized in agriculture and aquaculture to control plagues and aquatic parasites respectivamently. In spite of it low toxicity in mammals, this pesticide can be extremely toxic for fish. In this study, we evaluate the effects of a sub-lethal concentration (7.3 μg L-1, 50% of LC50-96h) of deltamethrin (formulation BUTOX®CE25) on the in vivo cardio-respiratory function of Nile tilapia (Oreochromis niloticus), are species of high economic potential. The cardio-respiratory parameters (O2 uptake - V&O2 , respiratory frequency fR, gill ventilation - G V& , ventilatory tidal volume VT, O2 extraction from the ventilatory current EO2, and heart frequency fH) were measured in a group of intact fish (GC), under normoxic conditions, during 24 h. After this period, another group of fish (GE) was exposed to deltamethrin and kept under these conditions for another 24 h period. During these periods the cardio-respiratory variables were continuously monitored. In another series of experiments, a group of non-intoxicated fish (GCH) was exposed to normoxia (PwO2 ~ 140 mmHg) and subsequently submitted to graded hypoxia (PwO2 = 100, 70, 50, 30 and 20 mmHg), while the above cardio-respiratory variables were continuously measured. A fourth group (GEH) was exposed to deltamethrin and submitted to the same hypoxic leves. Just after the exposure to deltamethrin fish presented a reduction in 2 V&O (mLO2.kg-1.h-1) which recovered gradually and reached initial (control) values after 18 h. Meanwhile fR (breaths.min- 1) remained unchanged in response to the toxicant. The G V& (mLH2O.Kg-1.min-1), however, increased significantly in the first 6 h of exposure to deltamethrin, returning to the initial values after 9 h. The G V& increased as a consequence of a proportional enhancement in VT (mLH2O.kg-1.resp-1). Immediately after the toxicant administration, fish presented a significant reduction in fH (bpm) and this bradicardia remained for a period of 12 h, after which this variable returned to the control values. Fish exposed to deltamethrin and submitted to graded hypoxia presented a significant reduction in 2 V&O , while their critical oxygen tension (PcO2) increased in relation to the control group. This indicates impairment in the capacity of oxyregulation of intoxicated fish. Also during graded hypoxia G V& and VT of fish exposed to deltamethrin increased progressively, while fR did not change. The fH was significant lower (bradicardia) in all hypoxic tensions. In conclusion, when Nile tilapia is exposed to sub-lethal concentrations of deltamethrin (formulation BUTOX ®CE25), the cardio-respiratory variables of this species stabilize after about 24 h, indicating a fast recovery to the toxicity of this pesticide. The cardio-respiratory responses to hypoxia, however, are impaired by deltamethrine exposure, suggesting that an adequate aerobic metabolism is important in the detoxification of this pesticide.